Unraveling fungal species cultivated by lower attine ants - Urrea-Valencia, Salomé [UNESP]; Júnior, Rodolfo Bizarria [UNESP]; Kooij, Pepijn W. [UNESP]; Montoya, Quimi Vidaurre [UNESP]; Rodrigues, Andre [UNESP] (Springer Nature, 2023)
Fungus-growing attine ants rely on an obligatory nutritional mutualism with fungi. Most attine ant genera cultivate fungi in the basidiomycete tribe Leucocoprineae (Agaricales: Agaricaceae). Although fungal partners show high genetic diversity, only two fungal species cultivated by leaf-cutting ants were formerly described. This is partly due to the lack of sexual structures (basidiomata) which are rarely formed in ant colonies. Moreover, basidiomata from leucocoprinaceous fungi grown by lower attines have not been observed in field colonies, but only when induced in artificial media in the absence of the ants. Here, we obtained basidiomata growing on oatmeal agar from fungal cultivars of Mycocepurus goeldii and Mycetophylax morschi, two lower attine ant species found in different biomes in Brazil. Morphological and phylogenetic analyses allowed us to describe two new species, Leucocoprinus attinorum from M. goeldii and Lc. dunensis from M. morschi. The new descriptions are the first to set formal names for Leucocoprineae fungi cultivated by lower attines and highlight the importance of in vitro cultures as a tool to assess the largely hidden taxonomic diversity of mushroom species grown by these attines.
Keywords: Biodiversity; Fungiculture; Fungus-farming ants; Leucoagaricus; Leucocoprinus; Mutualism; New taxa